Evidence-Based Decision Making in Dentistry : Multidisciplinary Management of the Natural Dentition - Rosen, Eyal; Nemcovsky, Carlos E.; Tsesis, Igor (Springer International Publishing : Imprint: Springer, 2017)
This clinically oriented book covers all aspects of the evidence-based decision making process in multidisciplinary management of the natural dentition. The book opens by clarifying the principles of evidence-based decision making and explaining how these principles should be applied in daily practice. Individual chapters then focus specifically, and in detail, on endodontic, periodontal, and prosthetic considerations, identifying aspects that need to be integrated into decision making and treatment planning. Evidence-based decision making with regard to preservation of the natural tooth versus extraction and implant placement is then discussed, and a concluding chapter examines likely future trends in dentistry and how they may affect clinical decision making. The authors include leading endodontists, periodontists, and prosthodontists. Given the multidisciplinary and comprehensive nature of the book, it will be relevant and interesting to the entire dental community.
Keywords: Dentistry.; elektronické knihy; electronic books